2019
DOI: 10.1111/os.12510
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of MRI and Pathological Features of Giant Cell Tumor of Bone Boundary

Abstract: Objective To find new clues to reduce postoperative recurrence after intralesional curettage by studying MRI and pathological features of giant tumor of bone (GCTB) boundaries. Methods A retrospective study was performed in the departments of orthopaedic surgery and medical imaging at our hospitals from January 2006 to August 2016. A total of 16 GCTB patients confirmed by pathology were asked to participate in the present study. The age range was from 18 to 44 years (9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In our study, the lesion showed a non-homogeneous hypo-intensity to iso-intensity on T1WI and hyper-intensity on T2WI. Consistent with previous reports, MR images of bone GCT may suggest the presence of solid components with hypo-intensity to iso-intensity on T1WI and T2WI, caused by hemosiderin deposition or high collagen content[ 3 , 4 ]. On contrast-enhanced images, unlike malignant soft tissue tumors or GCT-ST tumors with diffuse cystic components located in the subcutaneous tissue[ 8 - 11 ], the solid region of the lesion was slowly enhanced like hypervascular tissue, in line with IHC performance such as in bone GCT and the findings in other benign soft tissue tumors[ 2 - 4 ].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the lesion showed a non-homogeneous hypo-intensity to iso-intensity on T1WI and hyper-intensity on T2WI. Consistent with previous reports, MR images of bone GCT may suggest the presence of solid components with hypo-intensity to iso-intensity on T1WI and T2WI, caused by hemosiderin deposition or high collagen content[ 3 , 4 ]. On contrast-enhanced images, unlike malignant soft tissue tumors or GCT-ST tumors with diffuse cystic components located in the subcutaneous tissue[ 8 - 11 ], the solid region of the lesion was slowly enhanced like hypervascular tissue, in line with IHC performance such as in bone GCT and the findings in other benign soft tissue tumors[ 2 - 4 ].…”
Section: Discussionsupporting
confidence: 88%
“…Imaging has always been an important examination for preoperative tumor evaluation, but most of the previous studies on GCTB focused on tumors of the extremities (53)(54)(55)(56), which led to many findings of indicators not applicable to the spinal tumors, such as the distance between the edge of the tumor and joint surface, "paintbrush borders" sign, destruction of posterior cortical bone, and depth of local tumor cell infiltration. Although the majority of GCTB lesions are located in the metaphysis and epiphyses of the long tubular bones, approximately one-third of tumors are located in the axial skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging provides great contrast between tissues and there is no pressure applied on the tissue. Image plane orientation can be set accurately, and with 3-D sequences, the imaging plane can be adjusted postimaging (re-slicing) 63,107 . However, how well the contrast in the MRI image corresponds with the actual borders of the tendon remains unknown, and, as a result, the MRI-based measurement may either underestimate or overestimate the tendon CSA.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%